2019
DOI: 10.32628/ijsrst119659
|View full text |Cite
|
Sign up to set email alerts
|

Point of Sale (POS) Network with Embedded Fingerprint Biometric Authentication

Abstract: The steady growth in electronic transactions has promoted the Automated Teller Machine (ATM) thereby making it the main transaction channel for carrying out financial transactions. Conventional method of identification based on possession of ID cards or exclusive knowledge like a social security number or a password are not all together reliable. However, this has also increased the amount of fraudulent activities carried out on Automated Teller Machines (ATMs) thereby calling for efficient security mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…The research findings revealed that this service offers customers a secure alternative for conducting daily transactions, reducing the reliance solely on the ATM card. The questionnaire results indicated a high demand among customers for a safer substitute for the card, indicating strong backing for the proposal, as it has the potential to mitigate issues associated with traditional ATM cards [36]. In 2019, Bataev published a paper aimed at evaluating the economic efficiency of specific devices.…”
Section: Reviewmentioning
confidence: 99%
“…The research findings revealed that this service offers customers a secure alternative for conducting daily transactions, reducing the reliance solely on the ATM card. The questionnaire results indicated a high demand among customers for a safer substitute for the card, indicating strong backing for the proposal, as it has the potential to mitigate issues associated with traditional ATM cards [36]. In 2019, Bataev published a paper aimed at evaluating the economic efficiency of specific devices.…”
Section: Reviewmentioning
confidence: 99%
“…Authors in [23] proposed an embedded fingerprint biometric authentication method for the POS network. Fingerprint biometric technology was combined with personal identification numbers (PINs) for authentication to improve security.…”
Section: Literature Reviewmentioning
confidence: 99%